Flammability limits: A review with emphasis on ethanol for aeronautical applications and description of the experimental procedure - Coronado, Christian J.R.; Carvalho, Joao A.; Andrade, Jose C.; Cortez, Ely V.; Carvalho, Felipe S.; Santos, Jose C.; Mendiburu, Andres Z. [UNESP] (Elsevier B.V., 2012)
The lower and upper flammability limits of a fuel are key tools for predicting fire, assessing the possibility of explosion, and designing protection systems. Knowledge about the risks involved with the explosion of both gaseous and vaporized liquid fuel mixtures with air is very important to guarantee safety in industrial, domestic, and aeronautical applications. Currently, most countries use various standard experimental tests, which lead to different experimental values for these limits. A comprehensive literature review of the flammability limits of combustible mixtures is developed here in order to organize the theoretical and practical knowledge of the subject. The main focus of this paper is the review of the flammability data of ethanol-air mixtures available in the literature. In addition, the description of methodology for experiments to find the upper and lower limits of flammability of ethanol for aeronautical applications is discussed. A heated spherical 20L vessel was used. The mixtures were ignited with electrode rods placed in the center of the vessel, and the spark gap was 6.4 mm. LFL and the UFL were determined for ethanol (hydrated ethanol 96% INPM) as functions of temperature for atmospheric pressure to compare results with data published in the scientific literature. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Flammability limits; Ethanol; Visual criterion; Pressure and temperature dependence